Percutaneous nephrostomy, feasibility of mid and anterior axillary line approach and its complications: an experience - Sundaram, Senthilnathan; Balasubramanian, Jayamurugan; Narayanasami, Mohan Babu; Vanga, Rajitha (International Journal of Research in Medical Sciences, 2019)
Background: Nephrostomy performed as an emergency procedure to drain the obstructed calyceal system is a lifesaving procedure. Posterolateral approach is usually done to access the avascular plane of Brodel to avoid hemorrhage. This study evaluates the feasibility and complications in percutaneous nephrostomies placed at mid and anterior axillary line entry sites as it was found to be easier approach. Methods: A prospective study with 126 percutaneous nephrostomies performed with Ultrasound guidance, using single puncture technique and 8.5F pigtail catheter. The complications rates were analyzed according to WHO guidelines. Results: The technical success rate was 98.4%. Three hemorrhagic complications (2.38%) were recorded without any major interventions. Increased incidence (11.9%) of transient hematuria was observed with five cases (3.9%) of infection at entry site. One case (0.79%) of peritoneal breech recorded with no significant intraperitoneal collection. Conclusions: Placement of Percutaneous Nephrostomy tube at mid or the anterior axillary line appears to be a feasible and easy approach, as its complications rates are within acceptable limits with an advantage of increased patient comfort.